Profil Lipid dan Kejadian Hipertensi - Karwiti, Witi; Nasrazuhdy, Nasrazuhdy; Rezekiyah, Sholeha; Nurhayati, Nurhayati; Asrori, Asrori (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the relationship between lipid profiles and the incidence of hypertension in the POSBINDU group at the Jambi City Health Center. The research method used in this research is observational analytics using a cross-sectional design involving 100 respondents who were randomly selected and met the sample requirements. This research was carried out from April to July 2023. Research data analysis used the chi-square test, where the statistical test results show a p-value < 0.05. The research results showed that of the 100 data samples, the most significant number of respondents based on gender were men (26.0% and women (74.0%). The results of the chi-square test showed that there was a relationship between cholesterol and triglyceride levels and the incidence of hypertension (p-value = 0.000). In contrast, BMI status, cholesterol levels, HDL levels, and LDL levels were not significant with the incidence of hypertension. The research conclusion was that the incidence of hypertension was related to triglyceride levels and not related to BMI status, cholesterol levels, HDL levels, and LDL levels. Keywords: Hypertension, Cholesterol, Body Mass Index, High-Density Lipoprotein, Low-Density Lipoprotein